Pengaruh Pemberian Motivasi Terhadap Semangat Hafalan Al-Qur'an Siswi Kelas X Agama 2 Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi Tahun Ajaran 2016/2017 - Munawir Munawir (IAI Darussalam, 2017)
This research is directed at three main points, namely (1) to find out how motivation, (2) to determine how the spirit of memorization of the Qur'an, (3) there any influence of motivation on the spirit of the Qur'an recitation. This study uses a questionnaire with analysis techniques Product Moment. The study population was all students of class X religions 2 Madrasah Aliyah Al-Amiriyyah amounting to 22 respondents as sample indeed. After analyzing the data collected, the researchers found that the provision of motivation (X) greatly affects the spirit of memorization of the Qur'an (Y) with a correlation value of 0.93 which indicates that this research is in excellent condition. Thus, it can be concluded that the motivating influence on the spirit of the Quran recitation class X student of religion 2 Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi